PENGGUNAAN SISTEM APLIKASI KEUANGAN TINGKAT INSTANSI (SAKTI) TERHADAP PENGELOLAAN KEUANGAN DAN KINERJA KEUANGAN POLITEKNIK ATI MAKASSAR - Riniyanti; Roswiyanti; Balele, Andi Bintang (LPPM Universitas Muhammadiyah Bulukumba, 2025)
This study aims to analyze the use of the Agency Level FinancialApplication System (SAKTI) on financial management and financial performance atthe Makassar ATI Polytechnic. Using a qualitative descriptive method with a sampleof ten (10) SAKTI users in the finance section and financial data on budget realizationfor 2019-2023. The results showed that the use of the Agency Level FinancialApplication System (SAKTI) increased the efficiency and effectiveness of financialmanagement at the Makassar ATI Polytechnic. Through the effectiveness ratio andefficiency ratio can provide an overview of efficient and effective financialperformance. Financial performance at Makassar ATI Polytechnic for the averageeffectiveness ratio shows 92.60% with the effective category and for the averageefficiency ratio shows 96.93% with the less efficient category.